Retorika Dakwah K.H Ahmad Bahauddin Nursalim Dalam Channel YouTube NU Online - Muhammad Luthfi Syaf; Ibrahim, Malik (Al-Hikmah Media Dakwah, Komunikasi, Sosial dan Kebudayaan, 2023)
This study aims to analyze the preaching rhetoric of K.H. Ahmad Bahauddin Nursalim (Gus Baha) on the NU Online YouTube channel. In this research, the researcher used descriptive qualitative research and discourse analysis methods. Data collection techniques in this study used observation and documentation. In the data validation technique, the researcher used the terms observation and reference coverage. The preaching rhetoric of K.H. Ahmad Bahauddin Nursalim uses the delivery method, namely, script, memorizing, speaking suddenly, and speaking without preparation. Based on the type of rhetoric using dialogue and monology in KH Ahmad's choice of words, Bahauddin Nursalin uses unofficial, official, and conversational languages. Based on the tone category, using simple language style and medium language style Based on the category of sentence structure using parallelism, antithesis, and repetition. Based on voice style, use a relaxed pitch, moderate loudness, a fast rate, and pause with apa and uh. Based on the style of movement using body posture in a sitting position, appearance of manners with a white shirt, white sarong, and black cap, facial expressions and hand movements match the conditions spoken on stage. KH Ahmad Bahauddin Nursalin's hand movements as support for the words spoken Eye gaze as a form of respect